Effect of Tea Cultivars on the Volatile Metabolite Profile and Key Odorants of Keemun Black Tea - LIU Yaqin, WANG Hui, ZHU Lin, LEI Pandeng, ZHOU Hanchen (Shipin Kexue)
To investigate the effects of tea cultivars on the aroma quality and volatile profile of Keemun black tea (KBT), headspace solid-phase microextraction coupled with gas chromatography-mass spectroscopy (HS-SPME-GC-MS) was compare the differences in the volatile components of KBT made by traditional process from three tea cultivars, namely, ‘Qimenzhong’ (KMZ), ‘Fuzao 2’ (FZ2) and ‘Wancha 4’ (WC4). Odor activity value (OAV), aroma character impact (ACI) value, aroma reconstitution and omission tests were used to identify the key odorants of KBT. The change of volatile components was also analyzed during KBT processing. By comparison with the National Institute for Standards and Technology (NIST) 11 database, retention index calculation and comparison with referencestandards, 102, 75, and 88 volatiles were detected in KMZ, FZ2, and WC4 black tea samples, respectively, of which 11 were identified as key characteristic odorants based on OAV > 1 and ACI > 1%. Aroma reconstruction and omission experiments showed that six aroma-active compounds, namely, geraniol, trans-β-ionone, benzeneacetaldehyde, linalool, hexanal and phenylethyl alcohol, were the largest contributors to KMZ aroma. Their relative contents varied among the cultivars. The greatest changes in these key compounds occurred during withering and drying stages and their changing trends during the processing of KBT were relatively consistent among the cultivars. This study enriches the basic theory of KBT flavor quality and lays a theoretical foundation for aroma quality control and targeted processing of KBT.